Pengembangan Sains Anak Usia Dini melalui Pendampingan Penggunaan Metode Pembelajaran Demonstrasi di TK Dewi Masyithoh 58 Grenden-Puger - Wahidah, Nur; Sabihah, Riyadotus; Karmila, Nikmatul (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2022)
ABSTRACT (ENGLISH) The low creativity and innovativeness of teachers in using learning methods in the classroom which impacts make students feel bored, which results in a decrease in children's learning enthusiasm so they do not focus on receiving material from the teacher. The purpose of this community service research is to be able to develop children's science knowledge and become a teacher's guide in using relevant learning methods. The method used is EBR (Empowerment Basic Research). The results of this service research are an increase in teacher knowledge of learning methods that are relevant to the subject matter. Increased skills possessed by Dewi Masyithoh 58 Kindergarten teachers in the use of demonstration learning methods, Increasing teacher motivation and enthusiasm in carrying out learning activities in the classroom, There is an undeniable improvement that teachers are very enthusiastic in preparing the media to be used and enthusiastic to participate in activities in mentoring and students are more active and enthusiastic in participating in learning activities on science material. And the conclusion is that this activity is going well so that it provides new knowledge for teachers in the use of learning methods that are relevant to early childhood science material and teachers are more active and enthusiastic in carrying out learning activities in the classroom. Then the researcher's advice for the teachers of Kindergarten Dewi Masyithoh 58 to continue to be enthusiastic and active in developing their knowledge related to learning methods, because this is one way so that educational goals can run effectively and efficiently ABSTRAK (INDONESIA) Rendahnya kreatifitas dan inovatif guru dalam menggunakan metode pembelajaran di kelas yang dampaknya menjadikan peserta didik merasa bosan, yang berakibat pada turunnya semangat belajar anak sehingga tidak fokus dalam menerima materi dari guru. Tujuan dari penelitian pengabdian masyarakat ini ialah agar mampu mengembangakan pengetahuan sains anak dan menjadi pedoman guru dalam menggunakan metode pembelajaran yang relevan. Metode yang digunakan ialah EBR (Empowerment Basic Research). Hasil dari penelitian pengabdian ini ialah Adanya peningkatan pengetahuan guru terhadap metode pembelajaran yang relevan dengan materi pelajaran. Meningkatnya ketrampilan yang dimiliki guru TK Dewi Masyithoh 58 dalam penggunaan metode pembelajaran demonstrasi, Menambah motivasi dan semangat guru dalam melakukan kegiatan pembelajaran di kelas, Adanya peningkatan yang tidak bisa dipungkiri bahwa guru sangat bersemangat dalam mempersiapkan media yang akan digunakan dan antusias untuk mengikuti kegiatan dalam pendampigan ini dan Peserta didik lebih aktif dan semangat dalam mengikuti kegiatan pembelajaran pada materi sains. Dan kesimpulannya ialah kegiatan ini berjalan dengan baik sehingga memberikan pengetahuan baru untuk guru dalam penggunaan metode pembelajaran yang relevan dengan materi sains anak usia dini dan guru lebih aktif dan semangat dalam melaksanakan kegiatan pembelajaran di kelas. Kemudian saran peneliti untuk guru TK Dewi Masyithoh 58 agar terus semangat dan aktif dalam mengembangkan pengetahuannya terkait metode pembelajaran, karena ini merupakan salah satu cara agar tujuan pendidikan dapat berjalan dengan efektif dan efisien.